Clinical Outcome of Anticoagulant Treatment in Head or Neck Infection–Associated Cerebral Venous Thrombosis. Issue 5 (May 2016) - Zuurbier, Susanna M.; Coutinho, Jonathan M.; Stam, Jan; Canhão, Patricia; Barinagarrementeria, Fernando; Bousser, Marie-Germaine; Ferro, José M.
Abstract : Background and Purpose—: Local infections of the head or neck are a cause of cerebral venous thrombosis. Treatment of infectious cerebral venous thrombosis with heparin is controversial. We examined whether this treatment was associated with intracranial hemorrhagic complications and poor clinical outcome. Methods—: We retrieved data from a prospective cohort study of 624 cerebral venous thrombosis patients. We compared patients with and without an infection of the head or neck and anticoagulated versus not anticoagulated. We examined death or dependency and new intracerebral hemorrhages. Results—: Six hundred four of 624 patients were eligible for the study. Fifty-seven patients had an infection of the head or neck (9.4%). Comparing data between infection and noninfection patients, the frequency of therapeutic doses of heparin was similar in both groups (82.5% versus 83.7%). New intracerebral hemorrhages were more common in patients with an infection (12.3% versus 5.3%; P =0.04), but death or dependency did not differ between patients with and without an infection (15.8% versus 13.7%). In patients with an infection of the head or neck, there was no significant difference in the frequency of new intracerebral hemorrhages and poor outcome between patients who did or did not receive therapeutic doses of heparin. Conclusions—: New intracerebral hemorrhages were more frequent in patients with an infection. The use of therapeutic doses of heparin did not seem to influence the risk of new intracranial hemorrhages or poor clinical outcome, but the number of patients who did not receive anticoagulation was too small to draw firm conclusions about safety of heparin in adults with cerebral venous thrombosis and an infection of the head or neck. Abstract : Supplemental Digital Content is available in the text.